Pharmacokinetics and Biologic Activity of Apixaban in Healthy Dogs - Herrera, Noelle D.; Birschmann, Ingvild; Wolny, Monika; Papich, Mark G.; Brooks, Marjory B.; Goggs, Robert (Frontiers in Veterinary Science, 2021)
Thrombosis is common in critically ill dogs and causes considerable morbidity and mortality. The direct factor Xa inhibitor apixaban is safe, efficacious and convenient in humans. This study aimed to determine the pharmacokinetics (PK), bioactivity, protein binding, and bioavailability of apixaban following intravenous (IV) and oral (PO) administration to healthy dogs. Six healthy, adult, mixed-breed dogs were administered apixaban 0.18mg/kg IV and then following a minimum 2-week washout period administered apixaban 0.2mg/kg PO. Dogs were monitored using an apixaban-calibrated anti-Xa bioassay, prothrombin time (PT) and activated partial thromboplastin time (aPTT) and tissue-factor thromboelastography (TF-TEG). Plasma apixaban concentrations were measured using liquid chromatography-tandem mass spectrometry. Concentration-time plots were constructed, and PK modeling performed using compartmental methods. Administration of IV and PO apixaban was well tolerated. Following IV administration, mean half-life was 4.1h, and volume of distribution was 177mL/kg. Apixaban was highly protein bound (98.6%). Apixaban concentrations and anti-Xa activity were highly correlated (R2 0.994, P<0.0001). Intravenous apixaban significantly prolonged PT at time points up to 1h, and aPTT at time points up to 0.25h post-administration. Coagulation times were positively correlated with apixaban concentrations (PT R2 0.599, P<0.0001; aPTT R2 0.430, P<0.0001) and TF-TEG R-time was significantly prolonged 0.25h post-administration. Following oral administration, mean bioavailability was 28.4%, lag time was 2h, time to Cmax was 5h and the apparent elimination half-life was 3.1h. Oral apixaban significantly prolonged PT at 4, 6 and 8h but aPTT and TF-TEG were not consistently affected by oral apixaban. Apixaban concentrations are best monitored using anti-Xa activity. Future studies should determine PK and bioactivity of other doses using commercial tablets and following multidose administration and establish safe, effective dosing ranges in sick dogs.